2017
DOI: 10.17148/ijarcce.2017.6140
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Acceptance of Mobile money Applications in Enterprise Management: A Case Study of Micro and Small Enterprise Owners in Kisumu Central Business District, Kenya

Abstract: The research aimed at determining factors influencing acceptance of mobile applications in enterprise management specifically testing whether relationship exists between demographic features, Perceived Usefulness (PU), Perceived Ease of Use (PEOU) and Perceived Risk (PR); and acceptance of mobile money payment among micro and small enterprises in Kisumu City, Kenya. The research exhibited descriptive correlational research design enabling the researcher to determine the strength of relationship between the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
3
5
1
Order By: Relevance
“…Their acceptance of e-money is more influenced by the enjoyment of using e-money, the information about e-money, and personal information credibility. In this case, the results of this study do not support previous studies that show that PU and PEOU positively influence users' intention to use (16), (17), (18), (19). However, the previous study supported the results of this study regarding the effect of PE (1), (20), and PC (3) on behavioral intention.…”
Section: Results and Findingscontrasting
confidence: 99%
“…Their acceptance of e-money is more influenced by the enjoyment of using e-money, the information about e-money, and personal information credibility. In this case, the results of this study do not support previous studies that show that PU and PEOU positively influence users' intention to use (16), (17), (18), (19). However, the previous study supported the results of this study regarding the effect of PE (1), (20), and PC (3) on behavioral intention.…”
Section: Results and Findingscontrasting
confidence: 99%
“…The evidence from the study findings revealed that security and Trust were found to have a significant positive influence on the use of mobile money services due to service interoperability. The result supports the findings of other studies that found identity theft and sending money to the wrong account acted as factors for accepting mobile money services (Omol & Abeka, 2017). Moreover, the study findings are similar to the one conducted by GSMA (2018), which found that data privacy and security impact trust are the critical concern of users when considering whether to use mobile money.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Mobile communication is an open environment; hence much care must be taken when transferring sensitive information, primarily when related to financial data (Abdullah & Abdul-Hadi, 2009). Identity theft and sending money to the wrong account acted as factors for accepting mobile money services (Omol, Abeka, & Wauyo, 2017). Maintaining consumer trust is critical to the growth of mobile money services.…”
Section: Security and Trust Associated With Mobile Servicesmentioning
confidence: 99%
“…The negative moderation of age in the relationship between performance expectancy and behavioral intention as well as effort expectancy and behavioral intention signifies that the gains from performance of a system and the ease of use of the system influences younger people more than the aged. This outcome of the study is also in line with the findings of Omol et al (2017) in Kenya where typical mobile money payment users were found to be relatively young.…”
Section: Structural Model Assessment and Hypotheses Testingsupporting
confidence: 89%
“…Therefore, our empirical results support the life-cycle theory in the sense that young people tend to consume more with the advent of the cashless system than the old people. Even though Nordin et al (2012) and Omol et al (2017) documented that the adoption of cashless system causes bankruptcy among the youth because of increasing consumption among them, those studies did not support their findings with any economic theory.…”
Section: Structural Model Assessment and Hypotheses Testingmentioning
confidence: 92%